Domination in Cayley graphs: A survey. Issue 1 (1st April 2019) - Tamizh Chelvam, T.; Sivagami, M.
Abstract: Let be a symmetric generating set of a finite group . Assume that be such that and satisfies the two conditions : the identity element and : if, then Given satisfying and define a Cayley graph with and . When, it is called as circulant graph and denoted by . In this paper, we give a survey about the results on dominating sets in Cayley graphs and circulant graphs.